PERAN UNIT TERMINAL INSPECTION SERVICE DALAM PELAKSANAAN PENGAWASAN TERHADAP FASILITAS LANDSIDE DI BANDAR UDARA TJILIK RIWUT PALANGKARAYA - Rahimuddin; Eri Suryanti (Universitas Sains dan Teknologi Komputer, 2023)
ABSTRACT, Terminal Inspection Service (TIS) officers when carrying out surveillance still often find facilities that are damaged or unfit for use, coupled with a lack of TIS personnel, totaling 3 people. This researcher aims to find out how the Terminal Inspection Service Unit carries out a monitoring system for landside facilities at airports and to find out what obstacles and efforts are faced by the Terminal Inspection Service Unit (TIS) when carrying out surveillance of airport landside facilities. This study uses a qualitative method. The tools used were data collectors with the results of observations, interviews and documentation at the Terminal Inspection Service (TIS) unit. Observations, interviews and documentation as supporting documents to answer the research question formulation, then used data validity tests and finally the researchers performed data analysis techniques. which consists of data reduction, Data Presentation and Drawing Conclusions. The results of this study indicate that 1) The control system carried out by Terminal Inspection Service (TIS) officers refers to PM 178 2015 concerning service standards for airport service users and refers to the Standard Operating Procedure (SOP) for the Terminal Inspection Service Unit (TIS) for facility supervision. carried out periodically every day this is done to ensure that every airport facility functions properly and is safe to use so that zero accidents do not occur in accordance with airport principles. 2) data obtained that Terminal Inspection Service officers are still experiencing problems, both constraints on coordination between divisions and constraints on facilities that are still inadequate in dealing with service users and constraints on the number of personnel totaling 3 people due to lack of human resources which makes TIS officers experience pressure such as boredom, fatigue caused by facilities that are often damaged, plus the number of personnel who are so few, numbering 3 people, of course, the need for a Human Resources (HR) budget to fix all of this, but currently the budget is not enough to repair all facilities and lack of personnel.